2018
DOI: 10.18632/aging.101454
|View full text |Cite
|
Sign up to set email alerts
|

Roles of three Es-Caspases during spermatogenesis and Cadmium-induced apoptosis in Eriocheir sinensis

Abstract: Functions of Caspases remain obscure in Crustacea. We studied the existence and participations of apoptosis-related factors in Eriocheir sinensis testis. Three Es-Caspases (Es-Caspase 3/ 7/ 8) in E. sinensis were cloned and characterized. We observed that three es-caspases mRNA had specific expression patterns during spermiogenesis, with weak signal around the nucleus and invaginated acrosomal vesicle in early-stage spermatids, became stronger in middle-stage, finally focused on the acrosomal tube and nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 66 publications
(85 reference statements)
1
13
0
Order By: Relevance
“…In addition, genes expressed in the different apoptotic pathways were detected in the present study [28,29]. First, the flow cytometry results found that the MMP depolarization rate increased significantly after 42 days starvation (Figure 8(c)).…”
Section: Death Receptor Pathway and Mitochondrial Pathwaysupporting
confidence: 56%
“…In addition, genes expressed in the different apoptotic pathways were detected in the present study [28,29]. First, the flow cytometry results found that the MMP depolarization rate increased significantly after 42 days starvation (Figure 8(c)).…”
Section: Death Receptor Pathway and Mitochondrial Pathwaysupporting
confidence: 56%
“…Caspases are activated to gain the full catalytic activity after being proteolytically cleaved to initiate apoptosis 51 . Es Caspase-3, -7 and -8 are characterized to play crucial roles in Cadmium-induced apoptosis 27 , and Es Caspase-3/7-1 and Es Caspase-3-like protein are found to be involved in innate immune response and induce apoptosis under pathogen stimulation 28,29 . IAPs inhibit such proteolytically activated caspases, and further regulate apoptosis 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The diverse caspase family members have also been discovered in various species of crustacean. For example, three caspases ( Es Caspase-3, -7 and -8) were characterized in E. sinensis to play crucial roles in Cadmium-induced apoptosis 27 , and two caspases ( Es Caspase-3/7-1 and Es Caspase-3-like) were involved in innate immune response under pathogen induced apoptosis 28,29 . In shrimp L. vannamei , there were four caspases ( Lv Caspase-2, -3, -4 and -5) identified to play role in the host defense against white spot syndrome virus 30 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Shaoxing duck ( Anas platyrhyncha ) testicles has also revealed the upregulation in the mRNA levels of Bak‐1 and caspase‐3, while downregulation of the Bcl‐2 level (Dai et al, 2019). Another in vivo study has shown the possible interaction of the caspase‐8‐caspase‐3‐p53 pathway with the intrinsic and extrinsic pathways of Cd‐mediated apoptosis during spermatogenesis in Eriocheir sinensis , a crustacean (Xu & Yang, 2018). Therefore, these studies represent the complexity of different apoptotic pathways through which Cd induces apoptosis of testicular germ cells in different species that will help us in elucidating a common mechanism of apoptotic induction by Cd in testes.…”
Section: Cadmium‐mediated Toxicity In Testesmentioning
confidence: 99%
“…A recent study in Shaoxing duck (Anas platyrhyncha) testicles has also revealed the upregulation in the mRNA levels of Bak-1 and caspase-3, while downregulation of the Bcl-2 level(Dai et al, 2019). Another in vivo study has shown the possible interaction of the caspase-8-caspase-3-p53 pathway with the intrinsic and extrinsic pathways of Cd-mediated apoptosis during spermatogenesis in Eriocheir sinensis, a crustacean(Xu & Yang, 2018).…”
mentioning
confidence: 94%